Discovery of novel immunotherapeutic drug candidates for sciatic nerve injury using bioinformatic analysis and experimental verification - Li, Shengyou; Yu, Beibei; Gao, Xue; Zheng, Yi; Ma, Teng; Hao, Yiming; Wu, Haining; Wei, Bin; Wei, Yitao; Luo, Zhuojing; Xia, Bing; Huang, Jinghui (Frontiers in Pharmacology, 2022)
Inflammation following nerve injury and surgery often causes peripheral nerve adhesion (PNA) to the surrounding tissue. Numerous investigations independently examined the prevention or inhibition of PNA, however, an intervention targeting macrophages has not been fully elucidated. Basement membrane (BM) genes are known to modulate central nervous system (CNS) inflammation, however, their activities in the peripheral nervous system (PNS) remains undiscovered. In this report, we carried out weighted correlation network analysis (WCNA) to screen for principal sciatic nerve injury (SNI) module genes. Once an association between the module and BM genes was established, the protein–protein interaction (PPI) and immune infiltration analyses were employed to screen for relevant BM-related immune genes (Itgam, SDC1, Egflam, and CD44) in SNI. Subsequently, using the DSigDB database and molecular docking, we demonstrated that Trichostatin A (TSA) interacted with key immune genes. TSA is known to enhance M2 macrophage expression and attenuate fibrosis. Nevertheless, the significance of the epigenetic modulation of macrophage phenotypes in dorsal root ganglion (DRG) is undetermined after SNI. In this article, we examined the TSA role in fibrogenesis and macrophage plasticity associated with DRG. We revealed that TSA enhanced M2 macrophage aggregation, inhibited fibroblast activation, and improved sciatic nerve regeneration (SNR) and sensory functional recovery (FR) after SNI. In addition, TSA suppressed M1 macrophages and enhanced M2 macrophage invasion within the DRG tissue. Furthermore, TSA dramatically reduced IL-1β and TNFα levels, while upregulating IL-10 level. In summary, this research revealed for the first time that TSA alleviates fibrosis in DRG by promoting an M1 to M2 macrophage transition, which, in turn, accelerates SNR.